2018
DOI: 10.1111/deci.12328
|View full text |Cite
|
Sign up to set email alerts
|

Speak their Language: Designing Effective Messages to Improve Employees’ Information Security Decision Making

Abstract: Employee disinterest in information security remains one of the greatest impediments to effective information security management programs. How can organizations enhance the persuasiveness of the information security messages used to warn employees of threats and encourage employees to take specific actions to improve their security? We use fear appeal theory and the elaboration likelihood model to argue that security messages presented using more personally relevant language are more likely to induce employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 94 publications
(182 reference statements)
1
19
0
Order By: Relevance
“…Employee behaviour is fundamental to corporate InfoSec capabilities across the phases of prevention, detection, and response (Baskerville et al, 2014). Unfortunately, despite more than a decade of research on the human side of organisational InfoSec, people are often still identified as the weakest link, rooted in disinterest in security threats and the behaviours that mitigate them (Johnston et al, 2019). Motivated by this disconnect, the current study extends the Overall, the findings shed new light on the motivational mechanisms underpinning end user engagement in organisational InfoSec.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employee behaviour is fundamental to corporate InfoSec capabilities across the phases of prevention, detection, and response (Baskerville et al, 2014). Unfortunately, despite more than a decade of research on the human side of organisational InfoSec, people are often still identified as the weakest link, rooted in disinterest in security threats and the behaviours that mitigate them (Johnston et al, 2019). Motivated by this disconnect, the current study extends the Overall, the findings shed new light on the motivational mechanisms underpinning end user engagement in organisational InfoSec.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced above, substantial progress has been made in identifying various drivers of different security behaviours that ultimately contribute to the organisation's InfoSec posture. Despite this, problems in the human side of organisational InfoSec continue to burden companies, often rooted in employee disinterest in security threats and the behaviours that mitigate them (Johnston et al, 2019). A review of the extant literature (Appendix A) reveals two traditions within this stream that may help explain the disconnect between scholarly productivity and performance in practice.…”
Section: Introductionmentioning
confidence: 99%
“…The potential negative outcomes associated with IS security threats may therefore be more difficult to grasp and anticipate. Prior studies especially conducted in work environments found that often users do not appraise IS security threats as causing them real levels of concern (Johnston et al, 2019).…”
Section: Recommendation #1: Measure the Level Of Concern About Is Security Threatsmentioning
confidence: 99%
“…and Johnston et al (2016) highlight the importance of personal relevance of the IS security threat. We would add that personalizing the content of threat messages and how it is expressed to targeted audiences is likewise important to enhance threat message effectiveness (Johnston et al, 2019;Tannenbaum et al, 2015;Webb et al, 2010). We propose six new manipulations to personalize IS security threat messages.…”
Section: Recommendation #3: Personalize Is Security Threat Messagesmentioning
confidence: 99%
“…Employees are widely recognized as the weakest link in an organization's cybersecurity practice. Yet current programs designed to improve employee security behaviors often fail because interventions are not viewed as personally relevant (Johnston et al, 2019a(Johnston et al, , 2019b. Our study addresses a significant gap in scientific investigations of user cybersecurity hygiene by providing direct financial incentives to motivate users to comply with organizational cybersecurity policies and procedures.…”
Section: Introductionmentioning
confidence: 99%